Analisis Dampak Terminal Bayangan Terhadap Kinerja Lalu Lintas di Bundaran Tugu Radin Intan Rajabasa Ruas Jalan Soekarno Hatta - Natar - Heriadi, Riyan; Herianto, Dwi; Sulistyorini, Rahayu (Universitas Lampung, 2021)
The impact of the shadow terminal has caused the congestion and the unrest for road users. This is due to side obstructions caused by pedestrians, buses, cars, and other transportation waiting and picking up passengers around the road, resulting in buildup around the shadow terminal. As a result of the accumulation around the shadow terminal, it caused traffic jams on the Soekarno Hatta - Natar road. In connection with the above problems, it is necessary to study the impact of the shadow terminal on the Soekarno Hatta - Natar road section which can then be compared with the performance of the Soekarno Hatta - Natar road in the absence of a shadow terminal, in order to find out how much traffic performance changes on Soekarno Hatta road - Natar due to the shadow terminal. Thus, this study aims to determine the performance of the Soekarno Hatta - Natar road when there is a shadow terminal and when there is no shadow terminal. The results of this study indicate that there is a change in the value of the side friction in the condition of the shadow terminal on Monday with an event weight of 314 events with a side drag in the absence of a shadow terminal of 213 events. The difference in the value of the side friction will result in a decrease in the value of road capacity, degree of saturation and level of road services. Key words : Road Performance, Side Obstructions, Degree of Saturation, Capacity, Level of Service.